Astaxanthin protects cognitive function of vascular dementia - Zhu, Ningwei (Behav Brain Funct, 2020)
OBJECTIVE: The purpose of this study was to evaluate the effect of astaxanthin (AST) on cognition function, inflammatory response and oxidative stress in vascular dementia (VD) mice. METHOD: VD mice model was established by left unilateral common carotid arteries occlusion (LUCCAO). Following LUCCAO, AST was intragastrically administered for 30 days. Object recognition test and morris water maze test were used to evaluate cognitive function. Hematoxylin and eosin staining was performed to observe the hippocampal neuron structure. Enzyme-linked immunosorbent assay kit and bicinchoninic acid kit were respectively adopted to measure IL-1β and IL-4 protein expression and superoxide dismutase (SOD) activity and malondialdehyde (MDA) content in hippocampus and prefrontal cortex. RESULTS: AST improved the discrimination ability of VD mice. The escape latency and path length of VD mice treated with AST were dramatically reduced. Besides, AST 200 mg/kg enhanced crossing platform time and the number of times crossing the platform quadrant, and alleviated the morphological impairment in VD mice. Moreover, we found that AST inhibited IL-1β expression and MDA content, whereas promoted IL-4 expression and SOD activity in a dose-dependent manner. CONCLUSION: AST could improve cognitive impairment and hippocampal neurons in VD mice, which may be related to suppression of inflammatory response and oxidative stress.